The poetics of the gaze in contemporaneity - Pedrosa, Célia (Literatura e Sociedade, 2005)
This article aims at examining the poetic production of Paulo Henriques Britto, Eucanaã Ferraz and Fabio Weintraub, by focussing on the modes of configuration of an experience of the gaze in each. In order to do that, it relates discursive procedures and plastic resources employed in the composition of the covers of theirs books, looking to them as forms of representation both of an aesthetic choice as to lyrical language and of an ethical-political value attributed to it.